The construction and acceptance of fascist discourses in the early 20th century: A construção e aceitação dos discursos fascistas no início do século XX (Revista de História da UEG (REVHIST), 2023)
Currently, the fascist movement is still a very controversial topic, which generates several discussions among historians. Considering the great movement that took place within Europe in the first half of the twentieth century, having its origin in Italy and spreading to other countries, mainly in Germany, this study seeks to discuss how different interpreters of European fascism explained the construction and acceptance of the discourses fascists and the role of discourse in understanding the dynamics of these movements. We conclude that the two leaders preached the same ideology and used the same mechanisms and practically the same speeches to impose their ideas, in addition all the characteristics of the movement are very evident within the speeches, as well as the similarities of the ideals of the two leaders.Keywords: Fascism. Speech. Mussolini. Hitler.